2022
DOI: 10.1142/s011611052250007x
|View full text |Cite
|
Sign up to set email alerts
|

Institutions and the Rate of Return on Cattle: Evidence from Bangladesh

Abstract: This study extends the recent debate on the rate of return on cattle rearing in India, triggered by Anagol, Etang, and Karlan (2017) and followed by others, to the Bangladeshi context and finds that the apparent paradox of widespread cattle rearing despite negative returns in India is absent in Bangladesh. We use a nationally representative two-year panel data for rural Bangladesh and find that the average and marginal returns on raising cows and bullocks are positive and high in both 2011 and 2015. We show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The result revealed that earning from cattle reduced market inefficiency. The result is associated with [43,103]. Earnings from cattle might include transportation costs, broker's costs, feeding costs, and labour, which might cover a portion of the nurturing and other commercialization costs of cattle.…”
Section: Plos Onementioning
confidence: 99%
“…The result revealed that earning from cattle reduced market inefficiency. The result is associated with [43,103]. Earnings from cattle might include transportation costs, broker's costs, feeding costs, and labour, which might cover a portion of the nurturing and other commercialization costs of cattle.…”
Section: Plos Onementioning
confidence: 99%